ANALISIS PENGARUH ETIKA KERJA ISLAM TERHADAP SIKAP KARYAWAN BAGIAN AKUNTANSI DALAM PERUBAHAN ORGANISASI (Studi Kasus pada Bank Umum Non Syariah di Wilayah Eks Karesidenan Banyumas Jawa Tengah) - Sari Suasana Dewi; Icuk Rangga Bawono (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2008)
The recent cases in accounting practice in bussiness area (Enron, WorldCom and Global Crossing) be the attention of this study. Work ethics being something important for repairing this bad condition. Accounting agents need a change to reach a fair accounting practice. This study investigated Islamic work ethics influences to accounting department worker’s attitudes towards organizational change. The different character and result from previous research be a motivation for this study.The study uses a sample of 31 accounting department workers from 8 non- shariah banking institutions in Ex Banyumas Resident Central Java (Purwokerto, Cilacap, Banjarnegara and Purbalingga). Data has been collected using instrument of Ali (1988) modified by Tasmara (2000) for Islamic work ethic and Dunham et.al. (1989) for attitudes toward organizational change. Structural Equation Modelling on PLS (Partial Least Square) based is employed to test the proposed hypotheses.This study hypothesizes that Islamic work ethic influences significantly both dimension of accounting department worker attitudes toward organizational change (cognitive, affective and behavioral tendency). The result of this study indicate that Islamic work ethic significantly and positively influences various dimensions of attitudes toward organizational change with coeficient determination (R-Square) point for each dimension are : 0,332; 0,382 and 0,183. Implications, limitations and lines of future research are discussed.Keywords: etika kerja islam, perubahan organisasi, eks karesidenan Banyumas